The role of Primary Health Care in health promotion in marginalized territories: A literature review (Research, Society and Development, 2025)
Primary Health Care (PHC) constitutes the first level of assistance in the health system, functioning as the main gateway for users and as a structuring axis of the care network. In the Brazilian context, social and territorial inequalities directly affect access to health services, especially in peripheral and vulnerable areas. In these territories, users often face additional barriers related to insufficient infrastructure, shortage of health professionals, lack of material resources, and weaknesses in the implementation of public policies. This study presents an integrative literature review covering publications from 2015 to 2025, available in the SciELO, LILACS, and Google Scholar databases, aiming to analyze the challenges and potentialities of PHC in peripheral areas. The main findings show that democratizing access to healthcare services, strengthening health promotion and prevention strategies, expanding Family Health Strategy coverage, and valuing multiprofessional teamwork are essential aspects to overcome inequities. It is concluded that strengthening PHC in territories marked by resource scarcity and ineffective public policies is indispensable for promoting equity, reducing inequalities, and addressing health problems.